Fuzzy Energy-to-Peak Filtering for Continuous-Time Nonlinear Singular System - Chang, Xiao-Heng; Qiao, Ming-Yang; Zhao, Xudong (IEEE transactions on fuzzy systems, 2022)
This article studies the energy-to-peak filter design problem for the continuous-time nonlinear singular system. A Takagi-Sugeno fuzzy model is constructed to represent the nonlinear plant. The article focuses on the fuzzy filter design for singular system, such that the formulated filtering error system is admissible (regular, impulse-free, and stable) and ensures the corresponding filtering performance in the singular system. By introducing a novel Lyapunov function, design conditions of the fuzzy filter for the continuous-time singular system are proposed in the light of linear matrix inequalities representations. Finally, a practical example and the relevant simulation results are provided to demonstrate the effectiveness and feasibility of the proposed energy-to-peak filter design approach.